Reúso de água no processamento de jeans na indústria têxtil - Fernandes, Alinne Kadidja de Sousa (2010)
This study aims to assess the potential for industrial reuse of textile wastewater, after passing through a physical and chemical pretreatment, into denim washing wet processing operations in an industrial textile laundry, with no need for complementary treatments and dilutions. The methodology and evaluation of the proposed tests were based on the production techniques used in the company and upgraded for the experiments tested. The characterization of the treated effluent for 16 selected parameters and the development of a monitoring able to tailor the treated effluent for final disposal in accordance with current legislation was essential for the initiation of testing for reuse. The parameters color, turbidity, SS and pH used were satisfactory as control variables and presents simple determination methods. The denim quality variables considered were: color, odor, appearance and soft handle. The tests were started on a pilot scale following complexity factors attributed to the processes, in denim fabric and jeans, which demonstrated the possibility of reuse, because there was no interference in the processes and at quality of the tested product. Industrial scale tests were initiated by a step control that confirmed the methodology efficiency applied to identify the possibility of reuse by tests that precede each recipe to be processed. 556 replicates were performed in production scale for 47 different recipes of denim washing. The percentage of water reuse was 100% for all processes and repetitions performed after the initial adjustment testing phase. All the jeans were framed with the highest quality for internal control and marketed, being accepted by contractors. The full-scale use of treated wastewater, supported by monitoring and evaluation and control methodology suggested in this study, proved to be valid in textile production, not given any negative impact to the quality the produced jeans under the presented conditions. It is believed that this methodology can be extrapolated to other laundries to determine the possibility of reuse in denim washing wet processing with the necessary modifications to each company.